Photosynthetic activity and metabolic profiling of bread wheat cultivars contrasting in drought tolerance - Ghaffar, Abdul; Hussain, Nadeem; Ajaj, Rahaf; Shahin, Suzan Marwan; Bano, Hussan; Javed, Muhammad; Khalid, Ayesha; Yasmin, Memoona; Shah, Kausar Hussain; Zaheer, Muhammad; Iqbal, Muhammad; Zafar, Zafar Ullah; et al. (Frontiers in Plant Science, 2023)
The rapid increase in population growth under changing climatic conditions causes drought stress, threatening world food security. The identification of physiological and biochemical traits acting as yield-limiting factors in diverse germplasm is pre-requisite for genetic improvement under water-deficit conditions. The major aim of the present study was the identification of drought-tolerant wheat cultivars with a novel source of drought tolerance from local wheat germplasm. The study was conducted to screen 40 local wheat cultivars against drought stress at different growth stages. Barani-83, Blue Silver, Pak-81, and Pasban-90 containing shoot and root fresh weight >60% of control and shoot and root dry weight >80% and 70% of control, respectively, P (% of control >80 in shoot and >88 in root), K+ (>85% of control), and quantum yield of PSII > 90% of control under polyethylene glycol (PEG)-induced drought stress at seedling stage can be considered as tolerant, while more reduction in these parameters make FSD-08, Lasani-08, Punjab-96, and Sahar-06 as drought-sensitive cultivars. FSD-08 and Lasani-08 could not maintain growth and yield due to protoplasmic dehydration, decreased turgidity, cell enlargement, and cell division due to drought treatment at adult growth stage. Stability of leaf chlorophyll content (<20% decrease) reflects photosynthetic efficiency of tolerant cultivars, while ~30 µmol/g fwt concentration of proline, 100%–200% increase in free amino acids, and ~50% increase in accumulation of soluble sugars were associated with maintaining leaf water status by osmotic adjustment. Raw OJIP chlorophyll fluorescence curves revealed a decrease in fluorescence at O, J, I, and P steps in sensitive genotypes FSD-08 and Lasani-08, showing greater damage to photosynthetic machinery and greater decrease in JIP test parameters, performance index (PIABS), maximum quantum yield (Fv/Fm) associated with increase in Vj, absorption (ABS/RC), and dissipation per reaction center (DIo/RC) while a decrease in electron transport per reaction center (ETo/RC). During the present study, differential modifications in morpho-physiological, biochemical, and photosynthetic attributes that alleviate the damaging effects of drought stress in locally grown wheat cultivars were analyzed. Selected tolerant cultivars could be explored in various breeding programs to produce new wheat genotypes with adaptive traits to withstand water stress.